ANALISIS KINERJA PEGAWAI DALAM PENGEMBANGAN SUMBER DAYA MANUSIA DI KEMENTRIAN ENERGI SUMBER DAYA MINERAL (STUDI KASUS DI DIREKTORAT JENDERAL MINYAK DAN GAS BUMI) - Nur Assyifa; Susi Sulandari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2015)
Humans have an important role in any activity / work in an organization or institution, as humans become planners, perpetrators and determining its form objectives of the organization / agency. The purpose is not possible without the active role of employees even though the means owned by institution are adequate. . In an organization or agency human resources (HR) employee is one factor to improve productivity performance of an organization or agency.Therefore, the necessary human resources that have high professionalism and competence as it can support the improvement of the performance of employees in an organization or institution. This study uses a quantitative analytical approach. Until that is used in this study were 82 respondents who are employees of the Directorate General of Oil and Gas. The analysis used isthe correlation coefficient . From the results of this study demonstrate the performance of the Directorate General of Oil and Gas classified in the category quite well that is equal to 73.8%. The magnitude of the relationship between motivation (X1) with employee performance (Y) is equal to 27.66%. Thenthe work discipline (X2) with employee performance (Y) is equal to 29.59%. Then between motivation (X1) and discipline (X2) affect employee performance (Y) simultaneously by 63.04%. These results indicate a significant relationship between motivation and discipline of work with employee performance.